The Impact of Indonesian Muslim Consumers Hedonic and Trust on the Online Purchase Intention with Attitude as Intervening Variable (Case Study at Shopee Marketplace) - Shally Nur Rasyida (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2021)
This study aims to analyze the hedonic influence and trust in online purchase intention with attitude as an intervening variable. The sample used 212 respondents who are Muslim consumers in Indonesia and have made a purchase online at shopee. The method of testing data through online questionnaires was carried out on 17 November - 6 December 2020. The analysis technique used SEM-PLS 3 (structural equation model-partial least square. The results found that the hedonic and attitudes have a positive and significant toward online purchase intention, whereas there is no influence on the direct relationship between hedonic and online purchase intention. Further, there is a positive and significant influence between trust and attitude. As well as the direct influence test between attitude and online purchase intention also has a positive and significant effect. This research is expected to contribute to online sellers in the market to find out online purchase intentions for consumers, as well as become an insight for Muslim consumers to differentiate between their needs and desires in consuming according to Islamic teachings.